Newly found tombs at the north-eastern outskirts of Artashat - Gyulamiryan, Hayk (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The up to date ongoing excavations initiated by the Artashat archaeological expedition of the Institute of Archaeology and Ethnography of the Academy of Sciences of the Armenian SSR in 1970 revealed the significant role the capital played in the cultural, economic and political life of Antique Armenia as well as in the Near East. The systematic study of the site enabled to elucidate various spheres of urban life, including the burial types and some rituals linked to them which stand out and are widespread in this territory in the Antique period.